2009
DOI: 10.1007/s00401-009-0523-2
|View full text |Cite
|
Sign up to set email alerts
|

Staging/typing of Lewy body related α-synuclein pathology: a study of the BrainNet Europe Consortium

Abstract: When 22 members of the BrainNet Europe (BNE) consortium assessed 31 cases with a-synuclein (aS) immunoreactive (IR) pathology applying the consensus protocol described by McKeith and colleagues in 2005, the inter-observer agreement was 80%, being lowest in the limbic category (73%). When applying the staging protocol described by Braak and colleagues in 2003, agreement was only 65%, and in some cases as low as 36%. When modifications of these strategies, i.e., McKeith's protocol by Leverenz and colleagues from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
258
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 267 publications
(267 citation statements)
references
References 30 publications
6
258
0
3
Order By: Relevance
“…Full individual demographic data can be found in supplementary Table 1. Preliminary experiments showed that the post-mortem interval did not affect the signal of PAR2 in brain ( Supplementary Fig 1). The clinical diagnosis of Parkinson's disease was confirmed post-mortem by neuropathological analysis and the degree of α-synuclein was rated and each case was allocated an α-synuclein Braak stage (Alafuzoff et al, 2009;Braak et al, 2003). Control cases had no clinical diagnosis of a neurological or psychiatric disorder during life, nor any neuropathological abnormality evident post-mortem.…”
Section: Post-mortem Human Brainmentioning
confidence: 99%
“…Full individual demographic data can be found in supplementary Table 1. Preliminary experiments showed that the post-mortem interval did not affect the signal of PAR2 in brain ( Supplementary Fig 1). The clinical diagnosis of Parkinson's disease was confirmed post-mortem by neuropathological analysis and the degree of α-synuclein was rated and each case was allocated an α-synuclein Braak stage (Alafuzoff et al, 2009;Braak et al, 2003). Control cases had no clinical diagnosis of a neurological or psychiatric disorder during life, nor any neuropathological abnormality evident post-mortem.…”
Section: Post-mortem Human Brainmentioning
confidence: 99%
“…Both cortical and subcortical AS pathologies have been suggested to be the main determinant [693,694], whereas others suggested AD pathology to be more important, particularly when the Aβ load may be similar to that in AD [695]. The severity and extent of AS are variable, and according to revised guidelines are scored semiquantitatively in specific brain areas [593,[696][697][698][699]. AD pathology is a consistent but not universal finding in both disorders, differentiating two types of DLB: The "common form" is characterized by abundant neocortical senile plaques and NFTs in the limbic cortex; while "pure DLB" shows minimal AD lesions [700].…”
Section: Relationship Between α-Synuclein and Lewy Pathologymentioning
confidence: 99%
“…When the most severe stages of the progression are reached, these altered proteins were considered to be causative of NDDs such as AD, PD, DLB, FTLD-TDP and ALS. (27)(28)(29)(30)(31)(32)(33) Recently, a new entity, primary age-related tauopathy (PART), which describes neurologically unimpaired aged subjects with HPt pathology in the hippocampus, has been defined. (34) It has even been debated whether subjects with PART represent an early stage of AD or merely reflect a neurodegenerative process at an early stage.…”
Section: Aging and Nddmentioning
confidence: 99%